"I disagreed with a lot of values": Exploring Black immigrant agency in ethnic-racial socialization. (November 2021) - Thelamour, Barbara; George Mwangi, Chrystal A.
Abstract: Ethnic-racial socialization is a mechanism through which immigrant parents instill in their children a sense of pride in their culture while preparing them for negative experiences with racial and cultural out-groups. For Black immigrant parents, this can include promoting a wariness of Black Americans in their children. Through this lens, we investigated an understudied intercultural dynamic via interviews with 12 first- and second-generation African and Caribbean immigrants. Using deductive and inductive analyses, we first examined the socialization messages they received about Black Americans from their parents, finding that in addition to messages inculcating ethnic and cultural pride, the participants also heard warnings about affiliation with Black Americans. Those messages relied on personal experiences and harmful stereotypes. Second, emergent from the data were examples of the ways the participants rejected their parents' warnings. Experiences outside of the home appeared to influence views that were alternative to their parents. This novel finding provides avenues for future research investigating Black immigrants' paths to a sense of connection or distancing from Black Americans.